2010
DOI: 10.1175/2009jpo4232.1
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Mediated Enthalpy Flux to the Atmosphere and Salt Flux to the Ocean in High Winds

Abstract: Forecasts for the intensity and intensity changes of tropical cyclones have not improved as much as track forecasts. In high winds, two routes exist by which air and sea exchange heat and momentum: by spraymediated processes and by interfacial transfer right at the air-sea interface, the only exchange route currently parameterized in most storm models. This manuscript quantifies two processes mediated by sea spray that could affect predictions of storm intensity when included in coupled ocean-atmosphere models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…As with most such algorithms, inputs are sea surface temperature and salinity; barometric pressure; and surface-level values of wind speed, air temperature, and humidity. Besides the heat fluxes plotted in Figure 9, our algorithm also predicts the surface stress or friction velocity (u * ,B ) and both the interfacial and spray components of the enthalpy, salt, and freshwater fluxes (Andreas 2010). Our work on the vertical structure of the coastal zone boundary layer off of the East Coast of the U.S. reveals a different type of low-level wind maximum than for the extensively studied jets on the West Coast.…”
Section: Impact/applicationsmentioning
confidence: 88%
See 2 more Smart Citations
“…As with most such algorithms, inputs are sea surface temperature and salinity; barometric pressure; and surface-level values of wind speed, air temperature, and humidity. Besides the heat fluxes plotted in Figure 9, our algorithm also predicts the surface stress or friction velocity (u * ,B ) and both the interfacial and spray components of the enthalpy, salt, and freshwater fluxes (Andreas 2010). Our work on the vertical structure of the coastal zone boundary layer off of the East Coast of the U.S. reveals a different type of low-level wind maximum than for the extensively studied jets on the West Coast.…”
Section: Impact/applicationsmentioning
confidence: 88%
“…Meanwhile, the spray terms (H L,sp , H s,sp , Q en,sp ) in our full flux model require extensive microphysically based calculations, as described by Andreas and DeCosmo (2002), Andreas et al (2008), and Andreas (2010). Using the datasets we have assembled (summarized in , we can evaluate this hypothesized flux algorithm.…”
Section: Work Completedmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore begin this formal treatment of how and whether sea spray might influence the rate of air-sea gas transfer following the approach that Andreas and colleagues used for assessing how sea spray affects air-sea heat and moisture transfer [9,[27][28][29][30][31]. Microphysical modeling of the temperature and radius evolution of individual spray droplets underlies most of this work [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Foam layers on ocean surfaces due to breaking waves have attracted interest in the past decades for its various applications in geophysical parametric retrievals [1], climate modeling [2], and ocean wind sensing, among several others. Studies have shown that a foam layer profoundly affects the microwave emission from a sea surface; its presence increases the effective emissivity of the sea surface [3].…”
Section: Introductionmentioning
confidence: 99%